Соціально-політичні аспекти впливу на діяльність харчових підприємств в Україні - Basiurkina, Natalia; Konstantynova, Tatyana (Dr. Viktor Koval, 2017)
Introduction. The actuality problem of the chosen topic is due to a large practical the importance of the activities and development of food businesses in Ukraine under the influence of socio-political factors of the present. Existing tools for assessing the impact of socio-political factors in the overwhelming majority are based on uncertain approaches and do not pay much attention to considering these factors and their impact on the activities and development of the food business. Aim and tasks. Investigated, grouped and the list of socio-political aspects that affect the planning of enterprise development is given. The essence of socio-political aspects is defined in the modern sense from the point of view of introduction of social, political and economic factors of influence on the activity and development of food enterprises of Ukraine. The complex of measures for improvement and improvement of development of the food enterprise in the present economic and political situation is offered. These measures are aimed at supporting the economic initiatives of food business managers and include entrepreneurship support tools. A number of socio-political tools are proposed, as well as PEST analysis to ensure the strategic development of food businesses. Research results. In our opinion, the socio-political environment is perhaps the least predictable element in the entire business environment. Thus, the functions that are implemented during the planning process are substantially changed, the role of planning for development in the food business system is changing. It is increasingly becoming a tool for increasing the competitiveness of enterprises, a means of bringing together different food companies around new values and long-term priorities. Conclusions. Such an intensification of strategic planning, on the one hand, is a logical stage in the development of enterprises, on the other hand, by the efforts of these enterprises to find adequate tools and mechanisms for responding to the challenges in the country and in the world, when processes are significantly accelerating, including political, economic, social, technological, ecological etc. An additional measure of the current situation is the development of an information society that generates a number of new types of activities that managers should take into account for the sake of sustainable development of food businesses.